1992
DOI: 10.1001/archsurg.1992.01420040106019
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Mediators, Infection, Sepsis, and Multiple Organ Failure After Severe Trauma

Abstract: The relation of (multiple) organ failure (OF) to the release of inflammatory mediators and the incidence of infection and sepsis was studied prospectively in 100 patients with multiple trauma (injury severity score = 37). Sixteen patients died of OF, 47 patients survived OF, and 37 patients had no OF. Fifteen (24%) of the patients with OF showed no signs of infection. In patients with early onset of OF (n=45), infection followed with a lag of 2 or more days. In 16 (44%) of these patients, infection led to a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
9

Year Published

1993
1993
2002
2002

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(79 citation statements)
references
References 22 publications
2
68
0
9
Order By: Relevance
“…Indeed, plasma levels of neopterin have The study was performed in human beings in vivo. This been used as a marker of the severity of inflammation in has obvious advantages, including clinical relevance, and clinical practice [33][34][35]. It would be interesting to dein this study it was possible to detect cytokine-induced NO termine whether induction of GTP cyclohydrolase 1 in generation which has not been seen when cytokine-exother cells also increases NO generation from constitutive posed human veins were studied in vitro [5].…”
Section: 4mentioning
confidence: 99%
“…Indeed, plasma levels of neopterin have The study was performed in human beings in vivo. This been used as a marker of the severity of inflammation in has obvious advantages, including clinical relevance, and clinical practice [33][34][35]. It would be interesting to dein this study it was possible to detect cytokine-induced NO termine whether induction of GTP cyclohydrolase 1 in generation which has not been seen when cytokine-exother cells also increases NO generation from constitutive posed human veins were studied in vitro [5].…”
Section: 4mentioning
confidence: 99%
“…20 " 24 Elevated plasma levels of elastase have been described in patients with sepsis and correlated with morbidity and mortality of these patients. 25 " 30 Although in vitro studies suggest an upregulation and activation of PMN by TNF-α, IL-lß, and IL-8, the interactions between altered release of these cytokines and elevated elastase secretion by PMN during sepsis remain to be determined. Therefore, it was the objective of this study to investigate whether PMN activation determined by the release of elastase is dependent on increased synthesis and secretion of inflammatory cytokines in whole blood from patients with sepsis.…”
Section: Statisticsmentioning
confidence: 99%
“…Moreover, the studies showed without doubt that, in patients who have incurred severe infection followed major surgery or trauma, the underlying cellular and humoral biochemical events are quite similar regardless of the etiology of the insult. The clinical outcome seems to be only due to the magnitude of the inflammatory response, which is of course highest when trauma is superimposed by infection (Waydhas et al 1992).…”
Section: Discussionmentioning
confidence: 99%